Baltic Iron in the Atlantic World in the Eighteenth Century - Evans, Chris (The Atlantic World, 2007)
This book looks at the one of the key commercial links between the Baltic and Atlantic worlds in the eighteenth century - the export of Swedish and Russian iron to Britain - and its role in the making of the modern world.; Readership: All those interested in Atlantic history, the history of the Baltic, the history of technology, the history of economic thought, and material culture in the eighteenth century.